BRACIA TUŁODZIECCY – PRZYCZYNEK DO BIOGRAFII - Dobrzeniecka, Monika (Saeculum Christianum. Pismo Historyczne, 2017)
The aim of the article is to portray the heroes of Sierpc from the first half of 20th century: Henry, Edward and Felician Tulodziecki. It comprises a synopsis of their activity in the fields of education and politics, including their participation in the structures of Polish Socialist Party.